ChemInform Abstract: A General and Enantioselective Approach to Pentoses: A Rapid Synthesis of PSI‐6130, the Nucleoside Core of Sofosbuvir. Issue 42 (14th October 2014) - Peifer, Manuel; Berger, Raphaelle; Shurtleff, Valerie W.; Conrad, Jay C.; MacMillan, David W. C.
Abstract TiCl2(OiPr)2‐promoted condensation of silylketene acetals (I) and the enantioenriched aldehyde (II) produces esters of type (III) in good diastereoselectivity.